Non-fibrous inorganic particles in bronchoalveolar lavage fluid of pottery workers. Issue 11 (November 1996) - Falchi, M; Paoletti, L; Mariotta, S; Giosue, S; Guidi, L; Biondo, L; Scavalli, P; Bisetti, A
Abstract : AIM: To study the actual exposure of pottery workers to silica particles, as their risk of silicosis is potentially high because of the presence of inhalable crystalline silica particles in the workplace. METHODS: Nine pottery workers underwent bronchoalveolar lavage. The recovered fluid was analysed for cytological and mineralogical content by analytical transmission electron microscopy. The data were compared with those obtained from a control group composed of seven patients with sarcoidosis and six patients with haemoptysis. RESULTS: Cytological results showed a similar profile in exposed workers and controls, whereas in patients with sarcoidosis a lymphocytic alveolitis was found. Microanalysis of the particulate identified the presence of silicates, CRSs, and metals. Pottery workers had higher numbers of total particles and CRSs, and had a higher silicate/metal ratio. In five workers, the presence of zirconium silicate was also detected. Patients with sarcoidosis had the lowest number of particles, and an inverted silicate/metal ratio. CONCLUSION: Microanalysis by transmission electron microscope can provide useful information to assess occupational exposure to dusts.